MUSLIM GENERATION Z AND GLOBALIZED KNOWLEDGE: Perceptions of Muslim Generation Z of Banjarmasin on Prenuptial Agreement - Mansyuroh, Firqah Annajiyah; Haris, Muhammad; Mahmud, Hafini Bin (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
This article focuses on prenuptial agreement from the perspective of Muslims Generation Z in Banjarmasin City. The information abundancy falling this generation, including legal norms and legal culture in the borderless world, rises a question: is the perception of Muslims Generation Z in Banjarmasin in common with Generation Z in other cities in other countries? To answer this question, a survey method was used to explore the perception of Muslims Generation Z in Banjarmasin on prenuptial agreement. This research finds that the perception of Muslims Generation Z in Banjarmasin tends to be the same as Generation Z in America and England. They know and understand the function and purpose of the prenuptial agreement. They also opine that this agreement is to be carried out for the benefit of their marriage (in the future). In addition, this research also finds that the perception of Muslim Generation Z in Banjarmasin towards prenuptial agreements is substantively different from the perception of the previous generation in Indonesia, who consider a prenuptial agreement as a kind of taboo.[Artikel ini berfokus pada perjanjian pranikah dari sudut pandang Generasi Z Muslim di Kota Banjarmasin. Berlimpah-ruahnya informasi yang menghujani generasi ini, termasuk norma hukum dan budaya hukum di dunia internasional, menimbulkan pertanyaan: apakah persepsi Generasi Z Muslim di Banjarmasin sama dengan Generasi Z di kota lain di negara lain? Untuk menjawab pertanyaan tersebut, digunakan metode survei untuk menggali persepsi Generasi Z Muslim di Banjarmasin terhadap perjanjian pranikah. Penelitian ini menemukan bahwa persepsi Generasi Z Muslim di Banjarmasin cenderung sama dengan Generasi Z di Amerika dan Inggris. Mereka mengetahui dan memahami fungsi dan tujuan dari perjanjian pranikah. Mereka juga berpendapat bahwa perjanjian ini dilakukan untuk kepentingan pernikahan mereka (kelak). Selain itu, penelitian ini juga menemukan bahwa persepsi Generasi Z Muslim di Banjarmasin terhadap perjanjian pranikah secara substantif berbeda dengan persepsi generasi sebelumnya di Indonesia yang menganggap perjanjian pranikah sebagai hal yang tabu.]